Agronomic performance of 'Cabernet Sauvignon' with leaf removal management in a high-altitude region of Southern Brazil - Wurz D.A.* (2017)
The objective of this work was to compare the effect of different times of leaf removal on the vegetative-productive efficiency and on the chemical and physical characteristics of 'Cabernet Sauvignon' clusters in a high-altitude region of the state of Santa Catarina, Brazil. The experiment was conducted in the 2015 and 2016 vintages, in a commercial vineyard, located in the municipality of São Joaquim, in the state of Santa Catarina, at 1,230-m altitude. The treatments consisted of different times leaf removal in the cluster zone, in the following phenological stages: full bloom, buckshot berries, pea-sized berries, veraison, and 15 days after veraison, besides a control without leaf removal. The evaluated variables were subjected to the analysis of variance and compared with the Scott-Knott test, at 5% probability. In a high-altitude region, leaf removal provides more adequate indices for plant vegetative:yield balance. It also increases yield when performed during the pea-sized berry and veraison stages, increases the fertility index when performed during the pea-sized berry stage, and improves the chemical composition of 'Cabernet Sauvignon' grape when performed up to the pea-sized berry stage. The obtained results show the importance of early leaf removal to obtain must with potential for the production of quality wines.